India's role in the United Nations - Mody, Nawaz B.; Mehrish, B. N.; United Nations; University of Bombay. Department of Civics and Politics; National Seminar on "India's Role in the United Nations" (1995 : Bombay, India) (Bombay : Allied Publishers, 1995)
Papers presented at a National Seminar on "India's Role in the United Nations" organized by the Department of Civics and Politics, University of Bombay in January 1995.
"50th anniversary of United Nations, 1945-1995."
Includes bibliographical references and index.
"Select bibliography on India'a role in the United Nations": p. 239-250.
Keywords: United Nations -- India -- Congresses; Social surveys -- India -- Congresses